Ambient fine particulate matter air pollution and leisure-time physical inactivity among US adults. Issue 12 (December 2015) - An, R.; Xiang, X.
Abstract: Objectives: There is mounting evidence documenting the adverse health effects of short- and long-term exposure to ambient fine particulate matter (PM2.5 ) air pollution, but population-based evidence linking PM2.5 and health behaviour remains lacking. This study examined the relationship between ambient PM2.5 air pollution and leisure-time physical inactivity among US adults 18 years of age and above. Study design: Retrospective data analysis. Methods: Participant-level data ( n  = 2, 381, 292) from the Behavioral Risk Factor Surveillance System 2003–2011 surveys were linked with Wide-ranging Online Data for Epidemiologic Research air quality data by participants' residential county and interview month/year. Multilevel logistic regressions were performed to examine the effect of ambient PM2.5 air pollution on participants' leisure-time physical inactivity, accounting for various individual and county-level characteristics. Regressions were estimated on the overall sample and subsamples stratified by sex, age cohort, race/ethnicity and body weight status. Results: One unit (μg/m 3 ) increase in county monthly average PM2.5 concentration was found to be associated with an increase in the odds of physical inactivity by 0.46% (95% confidence interval = 0.34%–0.59%). The effect was similar between the sexes but to some extent (although not always statistically significant) larger for younger adults, Hispanics, and overweight/obese individuals compared with older adults, non-Hispanic whites or African Americans, and normal weight individuals, respectively. Conclusions: Ambient PM2.5 air pollution is found to be associated with a modest but measurable increase in individuals' leisure-time physical inactivity, and the relationship tends to differ across population subgroups. Highlights: We examined the effect of PM2.5 air pollution on physical inactivity in US adults. PM2.5 air pollution was found to increase the risk of physical inactivity. The effect of PM2.5 air pollution differed across population subgroups.